Explaining Pre-service Teachers’ Intentions to Use Technology-Enabled Learning: An Extended Model of the Theory of Planned Behavior - Hou, Mingdi; Lin, Yigang; Shen, Yafei; Zhou, Hui (Frontiers in Psychology, 2022)
This study proposed an extended theory of planned behavior to examine the factors that influence pre-service teachers’ intention to use technology-enabled learning, using constructivist pedagogical beliefs and information and communication technologies competencies as antecedent variables for attitudes, subjective norms, and perceived behavioral control. An online study was conducted with a random sample of pre-service teachers from seven universities in China, and 811 validated questionnaires were obtained. The results showed that the extended theory of planned behavior model explained 75% of the variance in intention; attitude, subjective norms, and perceived behavioral control had a positive and significant effect on intention. Furthermore, subjective norms had a positive and significant effect on attitude and perceived behavioral control. Constructivist pedagogical beliefs were the antecedent variables for attitude, subjective norms, perceived behavioral control, and information and communication technologies (ICT) competencies. ICT competencies were the antecedent variable for subjective norms and perceived behavioral control. Additionally, through multi-group analysis, this study found significant differences in path relationships between the lower and higher-grade groups. The effect of perceived behavioral control on intention diminished with increased grade level. The effect of subjective norms on perceived behavioral control reduced. The effect of constructivist pedagogical beliefs on attitude and perceived behavioral control on intention diminished. The effect of subjective norms on attitude increased. This study verified that adding the relationship between antecedent variables of theoretical factors and theoretical factors is an effective way to expand theory of planned behavior and provided a reference for future studies to focus on the related intention of pre-service teachers. Furthermore, it recommends that Chinese universities should eliminate the hindering influence of constructivist pedagogical beliefs, ICT competencies, attitudes, subjective norms, and perceived behavioral control in the process of preparing pre-service teachers. They should also pay attention to the individual differences of students in different grades and the problems that arise in the existing training.